EFEKTIVITAS MEDIA KIT MATEMATIKA UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA - Lestariningsih, Puji; Tawil, Tawil (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2015)
This research aims to determine the effectiveness of media kit mathto improve students? motivation. Desaign research is Classroom Action Research as much as two cycle of four meetings. This research procedure consists of four phases: planning, implementation, observation and reflection. This research subject is class 4 SDN Sambeng, Borobudur. as 12 students consisting of 7 man and 5 woman. Method of collection is done by observation of the students motivation. As the data analysis method used is the analysis of qualitative and quantitative data.Conclusions of this research are effectively used math media kit to increase students? motivation on the material fractions in grade 4 SDN Sambeng Borobudur Subdistrict ,District Magelang. With evidence that an increase in the average score of students motivation before action is taken at 15,16 into 27,66 after the action in cycle 2 or an increase of 82,5%.